Bioactive constituents in liposomes incorporated in orange juice as new functional food: thermal stability, rheological and organoleptic properties - Marsanasco, Marina (2015)
Liposomes were developed with bioactive constituents (omega-3, omega-6, tocopherol) incorporated in acid food. They were made of soy phosphatidylcholine (SPC) allowing the encapsulation of antioxidant vitamin C (VC) and tocopherol. Stearic acid (SA) or calcium stearate (CaS) was added as a bilayer stabilizer. The structural and oxidative stability of the liposomes were studied considering the heat effect of pasteurization. Size was analyzed by light scattering; shape and structure were studied by optical and transmission electron microscopy, respectively. Membrane packing was studied with merocyanine 540. Surface charge and oxidative stability were analyzed by zeta potential and ORAC method, respectively. The liposomes showed significant stability in all of the parameters mentioned above and an important protective effect over thermolabile VC. To confirm their applicability in food, the rheological behavior and a sensory evaluation of liposomes with vitamin C and bioactive constituents were studied. The sensory evaluation of liposomes in orange juice was performed by the overall acceptability and triangular tests with 40 and 78 potential consumers, respectively. The incorporation of all liposomal formulation did not change the acceptability of orange juice. Noteworthy, SPC and SPC:SA systems had rheological behavior similar to a Newtonian fluid whereas that SPC:CaS presented a pseudoplastic one, both considered excellent for larger scale production. From all the obtained results, we can conclude that these liposomal formulations are suitable for food industry applications, incorporating bioactive constituents and generating functional orange juice that conserves its bioactivity after pasteurization.